IMPLEMENTASI GERAKAN LITERASI UNTUK PENANAMAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI SD NEGERI JAKENAN - Solihin; Gimin; Azhar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the effect of E-learning implementation on teaching efficacy, students’ interest in learning, and the influence of students’ interest on teaching effectiveness. This research was a quantitative study using a questionnaire design, with a sample of 99 students from SMK (Vocational School) Negeri in Pekanbaru. Data were analyzed using path analysis, and the results indicated that the implementation of E-learning influenced students’ learning interest by 26.2%, which was categorized as a low influence because 73.8% was determined by other factors. E-learning implementation also influenced teachers’ teaching effectiveness by 25.7%, again in the low category because 73.7% was affected by other factors. Furthermore, students’ learning interest influenced teachers’ teaching effectiveness by 24.5%, with 74.3% determined by other factors. The combined contribution of E-learning and students’ learning interest to teaching effectiveness was 33.3%, still categorized as low, as 66.7% was influenced by other factors. Based on these findings, this study recommends that school observers and policy stakeholders actively conduct training, workshops, and other initiatives to improve E-learning, thereby enhancing students’ learning interest and teaching effectiveness.